Preliminary selection of area to implementation of a landfill at the city of Oliveira, Minas Gerais, Brazil | Seleção preliminar de área para implantação de um aterro sanitário no município de Oliveira-MG - Andrade, Lauren Costa; Ribeiro, Kátia Daniela (Revista Geama, 2016)
With the current population growth of cities, one of its major problems is the solid waste disposal. A landfill is the best solution to final disposal of solid waste; however, the selection of areas to implement the project is a difficult work. This paper presents the results of a preliminary selection of areas for the construction of a landfill at the city of Oliveira, Minas Gerais, Brazil. Three areas were evaluated through the area size, nearest population center's distance, urban center's distance, watercourse's distance, federal or state road's distance, vegetation type and land situation, analyzing advantages and disadvantages of each area for the implementation of a landfill. According to the evaluated criteria and the observed advantages and disadvantages during the preliminary selection, it was verified that the area 03 was the most suitable to receive the landfill, among selected areas.